2004
DOI: 10.1093/brain/awh315
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold low-frequency repetitive transcranial magnetic stimulation over the premotor cortex modulates writer's cramp

Abstract: Writer's cramp, or focal hand dystonia, is characterized by involuntary coactivation of antagonist or unnecessary muscles while writing or performing other tasks. Although the mechanism underlying this muscle overactivation is unknown, recent studies of changes in cerebral blood flow during writing have demonstrated a reduction in the activation of the primary motor cortex (MC) and hyperactivity of parts of the frontal non-primary motor areas. Therefore, any measures that decrease the activities of non-primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
165
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(174 citation statements)
references
References 70 publications
5
165
0
4
Order By: Relevance
“…In addition, it might be argued that immediate-TMS caused a change in cortical excitability that affected the subsequent deadaptation period. Although this is already unlikely given the low frequency (ϳ0.2 Hz) and number of pulses (192) (Murase et al, 2005), it is ruled out by the result that the delayed-TMS group was not similarly affected by the TMS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it might be argued that immediate-TMS caused a change in cortical excitability that affected the subsequent deadaptation period. Although this is already unlikely given the low frequency (ϳ0.2 Hz) and number of pulses (192) (Murase et al, 2005), it is ruled out by the result that the delayed-TMS group was not similarly affected by the TMS.…”
Section: Discussionmentioning
confidence: 99%
“…Low-frequency subthreshold repetitive TMS has been well-documented to reduce cortical excitability noninvasively. 5,20 This study was performed to test whether rTMS compared to sham stimulation improves clinical symptoms and normalizes electrophysiologic characteristics in patients with BEB. We found significant improvements with the C-and the H-coils immediately after stimulation for all 3 outcome measures and 1 hour after stimulation in physician rating and patient rating.…”
Section: 007) No Difference Was Found Between the Effects Of C Andmentioning
confidence: 99%
“…Earlier studies reported suppressive effects on cortical excitability at frequencies as low as 0.2 and 0.3 Hz. 5,12 We applied rTMS with 0.2 Hz, 180 stimuli, 15 minutes per session, with a stimulator output of 100% active motor threshold, which was assessed at the tibialis anterior muscle with the circular coil for the C-coil and S-coil conditions and with the H-coil for the H-coil condition. rTMS was delivered to the ACC in each session.…”
mentioning
confidence: 99%
“…8 In a recent study, lfrTMS over primary and secondary motor areas in an inhibitory stimulation mode was used to modulate writer's cramp. 9 Stimulation of the PMC but not of the primary motor cortex (MC) improved tracking errors, pen pressure, and prolonged TMS-induced silent periods.…”
mentioning
confidence: 99%